2022
DOI: 10.1186/s12916-022-02673-x
|View full text |Cite
|
Sign up to set email alerts
|

Population-based cohort study: proton pump inhibitor use during pregnancy in Sweden and the risk of maternal and neonatal adverse events

Abstract: Background Approximately half of all women suffer from heartburn at some stage during pregnancy. The most effective treatment is proton pump inhibitors, but the safety of use during pregnancy cannot be guaranteed. This study aimed to elucidate the effect of proton pump inhibitors on the risk of pre-eclampsia, gestational diabetes mellitus, preterm birth, an Apgar score at 5 min below 7, and a child being small or large for its gestational age. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…Only 3.3% of women used gastric acid inhibitors in the present cohort, of which approximately half are proton pump inhibitors 41 . Our findings suggest that gastric acid inhibitors may have a more important impact on postpartum depression than antibiotics.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Only 3.3% of women used gastric acid inhibitors in the present cohort, of which approximately half are proton pump inhibitors 41 . Our findings suggest that gastric acid inhibitors may have a more important impact on postpartum depression than antibiotics.…”
Section: Discussionmentioning
confidence: 54%
“…40 Only 3.3% of women used gastric acid inhibitors in the present cohort, of which approximately half are proton pump inhibitors. 41 Our findings suggest that gastric acid inhibitors may have a more important impact on postpartum depression than antibiotics. This could be related to a longer exposure period, making it the most important modifiable risk factor assessed in our study.…”
Section: Antibiotic Exposurementioning
confidence: 70%
“…And ranitidine also has a series of side effects, including contamination with N-nitrosodimethylamine (NDMA) ( Aldawsari, et al, 2021 ), shock ( Russom, et al, 2021 ) and cancer ( Cardwell, et al, 2021 ). In particular, ultra-dose use of PPIs, such as omeprazole and its derivatives, prolonged treatment duration between 1 and 5 years, and overprescription increase the risk of GI bleeding, pre-eclampsia, gestational diabetes, and preterm birth ( Bolek, et al, 2019 ; Breddels, et al, 2022 ). Several studies have highlighted the pathogenic drawbacks of PPIs in the medical treatment of GMI, since PPIs irreversibly inactivate H + /K + -ATPase activity by binding to cysteine 813, thus immobilizing the enzyme in the E2 configuration ( Shin, et al, 2011 ; Bruno, et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, a reduction in type 1 diabetes incidence was reported among those who smoked, though the authors do not recommend this as a public health intervention. Another population-based cohort study from Sweden reported potential harms associated with pregnant women taking proton pump inhibitors (a treatment for gastric reflux symptoms), including increased risks of preeclampsia, gestational diabetes and the birth of a small for gestational age infant [ 5 ]. Another large-scale study from Taiwan studied the potential risks for mothers of antenatal corticosteroid treatment to improve fetal health.…”
mentioning
confidence: 99%